Joseph Millerd Orpen’s ’A Glimpse into the Mythology of the Maluti Bushmen’: a contextual introduction and republished text - McGranaghan, M.; Challis, S.; Lewis-Williams, J. D. (Southern African Humanities, 2013)
Joseph Millerd Orpen’s article recounting the ethnographic data he collected from a Bushman informant (Qing) whilst searching for Langalibalele in the southern Maloti-Drakensberg is a key document for southern African archaeology, one of the cornerstones in the decipherment of the rock art of the region. This article publishes a slightly edited version of Orpen’s article with paragraph breaks and headings to facilitate the reading of this crucial document, as well as selections from Bleek’s Second report concerning Bushman researches and Lloyd’s A short account of further Bushman material collected that help situate Orpen’s work within the intellectual community of the nineteenth-century Cape Colony. The article also locates this work within the substantial corpus of Qing- and Orpen-related scholarly material, outlining the major uses made of the work thus far.